Relaciones entre CNR (Italia) y CONICET (Argentina): Notas para una historia - Lertora Mendoza, Celina Ana (2011)
CNR and CONICET have a partially shared history, both chronologically and thematically and institutionally. In this paper I will deal with only one aspect of institutional relations, which is becoming increasingly important in the process of scientific production: the joint research projects. Although scientific institutions of all countries have always tended to establish contacts and formal exchange networks of variable amplitude and complexity, the modality of joint projects is much more recent, and it could be said that, at the level of Europe-Latin America relations, it is barely 30/40 years old, that is to say, it has begun to be implemented when the system for the countries with the most homogeneous scientific production was already moderately consolidated.